Pengendalian Korosi Dengan Menggunakan Daun Nanas Sebagai Green Inhibitor Pada Baja ASTM A36 - Viona Aulia Rahmi; Komalasari Komalasari; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Corrosion is a decline quality of a metal because of chemical reaction a metal with its environment. The use of inhibitors is one way of corrosion control on metals, especially on the inside of the pipe. Pineapple leaf extract can be used as a green inhibitor. This study aims to utilize pineapple leaf extract as a green inhibitor about concentration of the inhibitor in controlling the corrosion rate by varying the time of the metal immersion. Extraction is done with a ratio of ethanol: distilled water, which is 1: 4. Research variations were corrosive media (0.1 M H2SO4), inhibitor concentrations (0, 2 gr/L) and immersion time (16, 32 and 48 hours). The method used is the weight loss method. The lowest corrosion rate in 0.1M H2SO4 solution is a concentration of 2 gr/L and a 48 hour immersion time of 20,686 mpy. The highest inhibitor efficiency in 0.1M H2SO4 solution concentration of 2 gr/L and time immersion for 48 hours amounted to 85.48%. It can be concluded that more inhibitors on corrosive media are able to produce low corrosion rates with high inhibition efficiency.Keywords: corrosion rate, inhibition efficiency, inhibitor, pineapple leaf